‘I Get High With a Little Help From My Friends’ - How Raves Can Invoke Identity Fusion and Lasting Co-operation via Transformative Experiences - Newson, Martha; Khurana, Ragini; Cazorla, Freya; van Mulukom, Valerie (Frontiers in Psychology, 2021)
Psychoactive drugs have been central to many human group rituals throughout modern human evolution. Despite such experiences often being inherently social, bonding and associated prosocial behaviors have rarely been empirically tested as an outcome. Here we investigate a novel measure of the mechanisms that generate altered states of consciousness during group rituals, the 4Ds: dance, drums, sleep deprivation, and drugs. We conducted a retrospective online survey examining experiences at a highly ritualized cultural phenomenon where drug use is relatively uninhibited- raves and illegal free parties. Engaging in the 4Ds at raves or free parties was associated with personal transformation for those who experienced the event as awe-inspiring, especially for people with open personalities (n = 481). Without awe, or a ritual context, indulging in the 4Ds was associated with a lack of personal growth, or anomie. A complex SEM revealed that personal transformation following awe-inspiring raves was associated with bonding to other ravers and prosocial behavior toward this group at a cost to self in a simple economic game. Bonding to humanity was not associated with these events. The findings suggest that employing the 4Ds in a ritualized environment - particularly dancing and drug use – can help build meaningful social bonds with associated positive behavioral outcomes.